2018
DOI: 10.1111/bph.14163
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in melatonin and 5‐HT signalling in the colonic mucosa of mice with dextran‐sodium sulfate‐induced colitis

Abstract: Our data suggest that DSS-induced colitis results in a reduction in melatonin availability and an increase in 5-HT availability, due to a reduction/loss of tryptophan hydroxylase 1 enzyme, 5-HT content and 5-HT transporters. Mechanosensory release was more susceptible to inflammation when compared with chemosensory release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…38 AhR in combination with these ligands can regulate expression of downstream target genes. 16 In this study, with the increase of dietary Trp, serum Kyn concentration, the mRNA and protein level of BD-2, the concentrations of IL-17, IL-22, and TNF-a in the jejunal and ileal mucosa were increased. IL-17, IL-22, and TNF-a are important pro-inammatory factors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…38 AhR in combination with these ligands can regulate expression of downstream target genes. 16 In this study, with the increase of dietary Trp, serum Kyn concentration, the mRNA and protein level of BD-2, the concentrations of IL-17, IL-22, and TNF-a in the jejunal and ileal mucosa were increased. IL-17, IL-22, and TNF-a are important pro-inammatory factors.…”
Section: Discussionmentioning
confidence: 54%
“…L-Trp plays important roles in protein synthesis and as a precursor of various bioactive compounds, such as kynurenine (Kyn) and 5-hydroxytryptamine (5-HT). 12,13 Thus, L-Trp might promote the expression of BD-2 in the epithelial cells through the following pathways: (1) activating the mTOR pathway via its intracellular receptors thereby promoting the expression of BD-2; (2) promoting the expression of BD via Kyn, which is as a ligand of aryl hydrocarbon receptor (AhR) can promote intestinal epithelial cell secretion of IL-22, IL-17, and other cytokines that enhance the expression of BD-2 in the intestinal epithelial cells via the NF-kB pathway; [14][15][16] or (3) promoting the expression of BD via 5-HT. In this study, Sprague Dawley rats were used to investigate the signalling pathways mediating Trp-promoted BD-2 expression in the rat intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has versatile functions, including antioxidant, memory formation, and blood pressure reduction qualities 32 . Additionally, many previous studies showed that oral and rectal administration of melatonin suppresses DSS-induced colitis [33][34][35] . Melatonin is abundant in the gut 15 , and pinealectomy has no influence on gut melatonin concentrations 36 .…”
Section: Discussionmentioning
confidence: 99%
“…5-HT signaling has been investigated in an animal model of intestinal inflammation, including 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis [ 96 ] and ileitis [ 5 , 97 , 98 , 99 ], dextran sodium sulfate (DSS)-induced colitis [ 4 , 100 ], and trichinella spiralis infection-induced intestinal inflammation [ 101 ]. Several studies have revealed that 5-HT is a key proinflammatory signaling molecule in gut inflammation because of the enhanced concentration of intestinal 5-HT and downregulation of SERT expression under intestinal inflammation [ 6 , 65 , 102 , 103 ]. Because of the knockout of TPH1 , the concentration of 5-HT in the GI tract was significantly reduced, followed by alleviation in clinical severity and histological damage scores by pharmacological adjustment of mucosal 5-HT in DSS- or dinitrobenzene sulfonic acid (DNBS)-induced colitis [ 104 ].…”
Section: Physiological and Pathophysiological Role Of Gut-derived 5-htmentioning
confidence: 99%
“…The physiological effects of 5-HT have been considerably investigated, and 5-HT has been reported to play a crucial role in GI regulation, particularly in intestinal motility and secretion [ 2 ]. The role of 5-HT in gut inflammation has also been widely investigated [ 4 , 5 , 6 , 7 ]. An increased concentration of 5-HT in the mucosa contributes to severe colitis.…”
Section: Introductionmentioning
confidence: 99%